2010
DOI: 10.2146/ajhp090626
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic hypothermia for out-of-hospital cardiac arrest

Abstract: TH is an effective strategy for improving neurologic outcomes of patients after out-of-hospital cardiac arrest due to VF. Further studies are needed to confirm the optimal time and methods for cooling to maximize the chance of complete neurologic recovery after cardiac arrest.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(28 citation statements)
references
References 74 publications
0
28
0
Order By: Relevance
“…Hypothermia is used clinically to promote neuronal survival in cardiac surgery and after cardiac arrest [63] by decreasing metabolic rate, reducing tissue oxygen consumption, depressing metabolic acidosis [64], suppressing calcium influx into neurons [65], and diminishing nitric oxide production [66]. Similar protective effects have been described during cochlear implantation, noise trauma and ischemic cochlear injury [6771].…”
Section: Potential Causes Of Hearing Loss Following Cochlear Implamentioning
confidence: 99%
See 1 more Smart Citation
“…Hypothermia is used clinically to promote neuronal survival in cardiac surgery and after cardiac arrest [63] by decreasing metabolic rate, reducing tissue oxygen consumption, depressing metabolic acidosis [64], suppressing calcium influx into neurons [65], and diminishing nitric oxide production [66]. Similar protective effects have been described during cochlear implantation, noise trauma and ischemic cochlear injury [6771].…”
Section: Potential Causes Of Hearing Loss Following Cochlear Implamentioning
confidence: 99%
“…Safe hypothermic induction can be noninvasive by using cooling blankets and ice packs, or a more invasive route can involve safe infusion of large volumes of cold fluids [63]. Hypothermia is used clinically to promote neuronal survival in cardiac surgery and after cardiac arrest [63] by decreasing metabolic rate, reducing tissue oxygen consumption, depressing metabolic acidosis [64], suppressing calcium influx into neurons [65], and diminishing nitric oxide production [66].…”
Section: Potential Causes Of Hearing Loss Following Cochlear Implamentioning
confidence: 99%
“…Another problem with surface cooling is cold injury, causing pressure ulcers and Therapeutic Hypothermia in Brain Injury 6 skin breakdown. Surface cooling is less efficient in reducing the temperature of target organs, such as the brain and heart 6 Invasive cooling 30 ml/kg Lactated Ringers solution that has been chilled to 4°C can be infused over 30 minutes. No adverse effects of the rapid infusion of this volume of IV crystalloid fluid in a study by Bernard.…”
Section: Surface Cooling: Dine Et Almentioning
confidence: 99%
“…Clinically significant cardiac arrhythmias occurred with less frequency in the Australian study compared to the European study, where no lidocaine was employed. 6 Coronary blood flow has been shown to decrease during mild hypothermia in patients with coronary artery disease. Evidence from animal studies has shown a 10% reduction in myocardial infarct size for every 1°C decrease in body temperature.…”
Section: Cardiovascular Manifestationsmentioning
confidence: 99%
See 1 more Smart Citation